SPECIFIC FEATURES OF THE INNOVATIVE DEVELOPMENT OF THE NATIONAL ECONOMY - Obidov Dilshod (Ecomind Press, 2025)
The innovative development of the national economy is one of the most important factors in ensuring economic growth and competitiveness in the modern era. The process of innovative development is a complex process aimed at increasing economic efficiency through the creation of new ideas, technologies, products and services, as well as improving existing production and management methods. This process is formed in accordance with the specific social, economic and cultural conditions of the national economy and is considered an integral part of the country's overall development strategy.